Warsaw's ambitious CSDP agenda: Polish Council Presidency seeks progress on Weimar Triangle initiatives - Claudia Major; Florian Wassenberg (Stiftung Wissenschaft und Politik (SWP), 2011)
With talk of the demise of the CSDP doing the rounds, is it perhaps surprising to see the Polish Council Presidency coming up with ambitious proposals as far-reaching as a civil-military headquarters for the EU. The agenda Poland has drawn up in close consultation with France and Germany (the Weimar Triangle) addresses a wave of security problems facing the EU's member states. Trapped between falling defence budgets and growing international challenges, states will have no alternative but to cooperate with one another. Poland hopes to revitalise the Common Security and Defence Policy as the defining framework for the EU's security policy. The Weimar Triangle should support Poland and push three pragmatic ideas: developing civil-military crisis response forces, setting up a military headquarters, and shared provision and use of military capabilities
Keywords: 320